Legal Implications of APHT Registered by PPAT More Than 7 (Seven) Working Days - Martini Martini; Takdir Takdir; Firman Muhammad Arif (UNES Law Review, 2023)
This research aims to analyze the legal implications of APHT registered by PPAT for more than 7 (seven) working days at the Luwu Regency Land Office. This research was conducted using Normative research methods. The data obtained, both primary data and secondary data, are categorized according to the type of data. The results of this research show that late registration of the Deed of Granting Mortgage Rights (APHT) will affect the birth time of the Mortgage Rights thereby causing losses for the parties, based on Article 23 paragraph (1) Law Number 4 of 1996 concerning Mortgage Rights, Officials Land Deed Makers (PPAT) will be subject to administrative sanctions, in the form of: verbal warning; written warning; temporary dismissal from office; dismissal from office. The guarantee itself provides legal protection for creditors. 4) Late registration of the Deed of Granting Mortgage Rights (APHT) does not cause the deed to be null and void.